COVID‑19 and the Performance of Exporting Companies in Benin - CHABOSSOU, AUGUSTIN FOSTER COMLAN; LOKONON, Boris Odilon; Nonvide, Gbêtondji Melaine Armel; AMEGNAGLO, Cocou Jaurès; AKPO, Laurent Gbedaso (My University, 2022)
This paper assesses the efect of the COVID-19 pandemic on the performance of exporting companies in Benin. It also identifes factors that explain the perceived efect of COVID-19 on the companies’ performance. To do this, we used a survey data covering 122 micro, small, and medium enterprises (MSMEs) and micro, small, and medium industry (MSMIs) in four communes in Benin. Firstly, we computed the annual rate change in quarterly turnover to capture the efect of the COVID19. Secondly, a multiple regression was estimated to identify factors explaining the perceived efect of the COVID-19 on the exporting companies. We found that the exporting companies experience on average a 53.308% drop in quarterly turnover in 2020 probably due to the COVID-19 crisis. Based on the forecasts, the results also revealed a very slow recovery in activities but the rate of change will remain negative until 2021 if nothing is done to support the MSMEs/MSMIs. Finally, we found that the perceived efect of the COVID-19 depends on the level of education of head of the companies, on the experience in exportation, and on the organization of the work because of the pandemic. Our fndings suggest the necessity for public policy support toward the MSMEs/MSMIs to contain the efect of the pandemic in Benin.
Keywords: Benin · COVID-19 · Exports · Enterprises · Performance